Education and science: current trends - Serebrennikova A. V., Goppe G. G., Kirgin D. S., Pokhomchikova E. O., Pogodaeva A. N., Baranov G. V., Khviiuzov M. A., Galashev A. N., Musina R. I., Danilchenko S. L., Rukina S. N., Amerzhanova Z. M., Isymov D. K., Kireeva E. V. (Education and science: current trends, 2017)
the implementation of modern fiscal policy is only possible under an active use of finance. They affect dynamic development of small businesses, taking into account its importance from the economic, political, scientific and technical and social points of view in market economy. The monograph presents the experience of the Rostov Region in the context of fiscal and taxation support, which is going to be useful for students, academics and practitioners. It is proposed to develop common criteria for granting state and tax support to small businesses, to establish a unified mechanism for collecting insurance premiums for all tax payers under special tax regimes, to improve certain elements of the patent taxation system, which activates the stimulating role of finance in the development of this sector.
Keywords: государственная программа; малый бизнес; специальные налоговые режимы; small businesses; state program; бюджетная поддержка; налоговая поддержка; budget support; fiscal support; special tax regimes